Improving Return on Investment for Photovoltaic Plants by Deploying Customized Load - Eid, Bilal M.; Islam, Md R.; Nahid, Abdullah Al; Kouzani, Abbas; Parvez Mahmud, M. A. (Institute of Electrical and Electronics Engineers Inc.)
The deployment of grid connected photovoltaic (PV) power plants is increasing dramatically recently. Due to the intermittent nature of the PV power plant, a battery and/or a power curtailment controller has to be installed to maintain the stability of the distribution network. The battery is an additional cost in the system so the return on investment (ROI) analysis has to be conducted. An alternative to the battery, a customized load can be used to consume the surplus energy. This load has to make an additional income to be profitable for the plant's owner. Such load can be crypto-currency mining rig that does calculation to validate the transaction in the Blockchain network. This study compared the ROI of the battery and the mining rig. The study shows that mining rig has higher ROI of 7.7% compared to 4.5% for battery. © 2020 IEEE.
Keywords: batteries; blockchain; mining rig; Photovoltaic power plants; return on investment